Factorise the quadratic using the method of completing the square to get it into the form $y=\left(x+a\right)\left(x+b\right)$y=(x+a)(x+b).

$y=x^2+4x+3$y=x2+4x+3

Easy

Approx 5 minutes

Sign up to try all questions

Factorise the quadratic using the method of completing the square or otherwise to get it into the form $y=\left(x-a\right)\left(x-b\right)$y=(x−a)(x−b).

$y=x^2-6x+8$y=x2−6x+8

Factorise the quadratic using the method of completing the square to get it into the form $y=\left(x+a\right)\left(x+b\right)$y=(x+a)(x+b).

$y=x^2+56x+159$y=x2+56x+159

Factorise the quadratic using the method of completing the square to get it into the form $y=\left(x-a\right)\left(x-b\right)$y=(x−a)(x−b).

$y=x^2-24x+63$y=x2−24x+63

Outcomes

NA6-5

Form and solve linear equations and inequations, quadratic and simple exponential equations, and simultaneous equations with two unknowns